Plagiarism in Portugal – Secondary Education Teachers’ perceptions - Dias, Paulo C. (2021)
Plagiarism is growing among students due to Internet easy access. This has generated several challenges to educational systems and teachers. This study aims to explore teacher's perceptions on plagiarism and present results from a sample of 67 Portuguese secondary education teachers. Results show that teachers attribute plagiarism to the easy access to Internet contents, student's lack of critical approach to analyze information, student's laziness and student's poor time management skills. The most common behaviors are copying amounts of text from books and Internet without referencing. The heaviest penalties are applied to collusion and text copy without referencing. To prevent plagiarism teachers suggest to address student's skills promotion, introduction of honor codes, and plagiarism detection software. Approaching plagiarism at school is urging and it is a way to avoid its occurrence.